Metal and body condition assessment in aquatic furbearers from the Porcupine River system, Timmins, Ontario - Stransky Ogilvie, Carlie N. (Laurentian University of Sudbury, 2020)
In 2014, MOECC, MNRF, local First Nations, the City of Timmins, and local mines designated the Porcupine Watershed, east of Timmins, Ontario, as an area of concern due to a variety of potential point-source contaminants from over a century of forestry, mining, and urbanization. Further study of the watershed was necessary to determine the existence and, if present, the extent of contamination. This study evaluated metal uptake and its relationship with body condition of Castor canadensis, Ondatra zibethica, Lontra canadensis, and Mustela vison. Results indicated that in the industrial area, Castor canadensis had an increase of 5% in body condition and 26% decrease in body condition in Ondatra zibethica. Moving up the trophic level, aquatic carnivores, Lontra canadensis had a 46% lower body condition in industrial areas, while Mustela vison’s body condition was lower in the industrial area by 33%. In both trophic levels, arsenic, cadmium, cobalt, copper, iron, and manganese levels in tissues were significantly higher (P<0.05) in the industrial area compared to the reference areas. These results indicate that bioavailability of certain metals is higher in the industrialized area of the Porcupine Watershed and that potentially, some pressures on fauna health may exist. No evidence of site-influence or enhanced levels were observed for mercury, lead, antimony, selenium, chromium or zinc. No direct link between higher point-source bioavailability of metals and current and past industry, urban development nor natural variability in local geology was found. However, if remedial measures are implemented, all parties should be involved. In order to protect and restore the health of the watershed, further investigation is necessary to determine the point- sources of the identified metals. Master of Science (M.Sc.) in Biology